PKM KARANG TARUNA TUNAS KARYA KUNCIRAN INDAH - Gilang Ryan Fernandes; Redo Abeputra Sihombing (Universitas Pahlawan Tuanku Tambusai, 2021)
This community service was carried out at Karang Taruna Tunas Karya Kunciran Indah, with the title